Embedding multinationals in postsocialist host countries: Social interaction and the compatibility of organizational interests with host-country institutions - Marta Kahancová (Max Planck Institute for the Study of Societies, 2008)
The internationalization of postsocialist countries brought about by the activities of multinational corporations (MNCs) has produced a growing diversity of actors capable of shaping work standards in these countries. The organizational and institutionalist literature on MNCs has concentrated only on the outcomes of such internationalization processes in terms of diffusing MNCs' organizational practices or adapting them to host-country conditions. This paper offers a theoretical and empirical scrutiny of the process through which MNCs establish and reinforce their position in host-country labor markets and societies. In particular, the focus is on how MNCs become legitimate actors in changing work standards in host-country labor markets, and how host-country actors (i.e., workers, trade unions, and the local society) become capable of shaping MNCs' organizational practices in postsocialist subsidiaries. This process is referred to as MNC embedding. Building on a qualitative case study of a Dutch MNC and its subsidiaries in Hungary and Poland, the paper theorizes and empirically documents how embedding occurs and what conditions facilitate it. It is argued that particular interaction dynamics in each MNC subsidiary studied account for the extent to which MNC embedding occurs via unilateral managerial decisions or with the involvement of local actors. Moreover, social interaction between MNCs and host-country actors facilitates institution building from below. This means that through social interaction MNCs become legitimate actors contributing to institution building in environments where broader institutional underpinnings of work practices and traditions of collective bargaining are less extensive than in continental Western Europe. – – Die Aktivitäten multinationaler Unternehmen forcieren die wirtschaftliche Internationalisierung postsozialistischer Länder. Hierdurch wächst in diesen Ländern die Vielfalt an Akteuren, die in der Lage sind, Arbeitsstandards zu entwickeln. Die organisationssoziologische und institutionalistisch orientierte Literatur zum Thema hat sich vor allem mit den Auswirkungen von Internationalisierungsprozessen auf die Verbreitung organisatorischer Praktiken der Unternehmen oder ihrer Anpassung an die Bedingungen des Aufnahmelands beschäftigt. Dieses Papier bietet nunmehr eine theoretische und empirische Untersuchung der Prozesse, durch die multinationale Konzerne ihre Position im Arbeitsmarkt und in der Gesellschaft des Aufnahmelandes finden und festigen. Das Hauptinteresse liegt auf der Frage, wie multinationale Unternehmen zu legitimen Akteuren werden, die Arbeitsstandards in postsozialistischen Beschäftigungsmärkten verändern können und wie die Akteure des Aufnahmelandes (Arbeiter, Gewerkschaften und die lokale Bevölkerung) in die Lage versetzt werden, die Praktiken dieser Unternehmen mitzugestalten. Dies wird als Prozess der Einbettung multinationaler Unternehmen gedeutet. Anhand einer qualitativen Fallstudie zu einem niederländischen Konzern und seinen Niederlassungen in Ungarn und Polen analysiert das Papier, wie es zu einer solchen Einbettung kommt und welchen Bedingungen sie unterliegt. Die Analyse zeigt, dass bestimmte Interaktionsdynamiken in allen untersuchten Niederlassungen auf unilaterale Managemententscheidungen oder die Einbeziehung lokaler Akteure zurückzuführen sind. Darüber hinaus erleichtert die soziale Interaktion zwischen Unternehmen und lokalen Akteuren die Institutionenbildung von der Basis aufwärts. Im Ergebnis werden multinationale Unternehmen durch soziale Interaktionen vor Ort zu legitimen Akteuren, die zur Institutionenbildung in einem Umfeld beitragen, in dem die Verankerung von Arbeitsstandards und Traditionen der Mitbestimmung weniger verbreitet ist als im Westen Kontinentaleuropas.
Keywords: 300